Konflik Internal Dalam Pencak Silat: Perspektif Hukum Progresif - SuJono; Wisnu Aryo Dewanto (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2024)
Ttraditional martial art that is rich in cultural and historical value, is often considered a symbol of unity and national pride in many Southeast Asian countries, including Indonesia. However, like other organizations or communities, martial art is also vulnerable to internal conflicts which can affect the organization itself and also have a negative influence on the surrounding environment. The purpose of this writing this article to determine the factors that cause internal organizational disputes, especially Petrsaudaraan Setia Hati Terate martial art organization in Madiun and solutions from Hukum Progresif. The research method that the author uses is Qualitative Research, namely by collecting data through observation and interviewing sources. The primary data source used is the martial artists in Madiun City, while the secondary data source used is PSHT trainers, ulama, community leaders, academics in Madiun and surrounding areas. Problems experienced by martial art organizations, especially PSHT leadership disputes in Madiun, can be resolved using Hukum Progresif theory with steps including mediation or dialogue, upholding human rights, fair distribution of human resources and adequate education for leaders. The causal factors are that individual PSHT members do not follow the rules of the organization. The claim of the validity of the recognition was because they were both students of different generations, so turmoil arose which led to conflict.